2012
DOI: 10.1121/1.3651093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nonlinear sound propagation on the characteristic timbres of brass instruments

Abstract: The capacity of a brass instrument to generate sounds with strong high-frequency components is dependent on the extent to which its bore profile supports nonlinear sound propagation. At high dynamic levels some instruments are readily sounded in a "cuivré" (brassy) manner: this phenomenon is due to the nonlinear propagation of sound in ducts of the proportions typical of labrosones (lip-reed aerophones). The effect is also evident at lower dynamic levels and contributes to the overall tonal character of the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 10 publications
0
24
0
1
Order By: Relevance
“…The string is obviously the most common case for string instruments sharing the two properties of nonlinear vibrations together with commensurable eigenfrequencies; see, e.g., [12,17,18,32]. Nonlinearities are also encountered in reed instruments such as saxophone and clarinette; see, e.g., [27] and brass instruments (see, e.g., [20]) and references therein. For percussion instruments, gongs, cymbals, and steelpans (or steeldrums) are also known for displaying geometric nonlinearity due to the large amplitude vibrations of the main shell structure.…”
Section: Introductionmentioning
confidence: 99%
“…The string is obviously the most common case for string instruments sharing the two properties of nonlinear vibrations together with commensurable eigenfrequencies; see, e.g., [12,17,18,32]. Nonlinearities are also encountered in reed instruments such as saxophone and clarinette; see, e.g., [27] and brass instruments (see, e.g., [20]) and references therein. For percussion instruments, gongs, cymbals, and steelpans (or steeldrums) are also known for displaying geometric nonlinearity due to the large amplitude vibrations of the main shell structure.…”
Section: Introductionmentioning
confidence: 99%
“…Rumbles are characterised by an extremely lowfundamental frequency(approx. [16][17][18])which directly reflects the extraordinary size of the elephant vocal folds [4]. Additionally,i nvestigations of the resonance frequencies of rumbles indicate that the trunk is involved in addition to the oral cavity in shaping the spectral envelope of most, butnot all, calls [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Akey parameter for predicting the severity of this nonlinear steepening is the critical shock length distance [15] associated with the profile of the initial source signal (F0, amplitude and wave shape). When the length of the bore approaches this critical value, as is the case in brass instruments played at fortissimo level, the strong distortion of wavesd uring their propagation inside the bore affects the spectral content of the radiated signal, conferring its distinctive brassy quality [17]. The exceptional length of the elephant'strunk opens up the possibility that the nonlinear steepening effect might be significant during elephant trumpeting, as in brass instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Myers et al [8] showed the sound generation mechanism for brass instrument. Different geometry variation and effects on radiated sound frequencies were investigated.…”
Section: Introductionmentioning
confidence: 99%